Effect of miR-381-3p/FGF7 axis on the osteogenic differentiation of bone marrow mesenchymal stem cells through MEK/ERK signaling pathway. (June 2022) - Qiu, Ling; Cai, Jiao; Zhang, Nan; Ma, Lei; Fan, Fang-yi; Li, Xiao-ming
Abstract: Although microRNAs (miRNAs) exert an important role in the osteogenesis of mesenchymal stem cells (MSCs), the effect of miR-381-3p on the osteogenic differentiation in MBD‑MSCs is still unclear. The BMMSCs from patients with MBD (MBD‑MSC) or normal participants (Normal‑MSC) were isolated and induced to differentiation with dexamethasone. BMMSCs were transfected with miR-381-3p mimic, miR-381-3p inhibitor, and FGF7 siRNA to regulate the expression of miR-381-3p or FGF7. The direct binding between miR-381-3p and FGF7 was predicted and confirmed by bioinformatics prediction and luciferase reporter assay. The effect of miR-381-3p on the osteogenic differentiation of BMMSCs was assessed by RT‑qPCR, alizarin Red S staining and western blot assays. Isolated BMMSCs showed the regular morphology, and were positive for CD44, CD90 and CD105 but negative for CD34 and CD45 markers. The calcium deposition and the relative mRNA expression levels of ALP, OC and OPN after induction were markedly enhanced. MiR-381-3p was upregulated in BMMSCs. Also, inhibition of miR-381-3p notably promoted osteogenic differentiation, vice versa. Besides, miR-381-3p could directly target FGF7 and negatively modulate the expression of FGF7. Moreover, inhibition of FGF7 attenuated the increase of the calcium deposition, and the relative mRNA expression of ALP, OC and OPN caused by the downregulation of miR-381-3p. In addition, the miR-381-3p inhibitor-induced the enhancement of the relative protein expressions of FGFR2, p-MEK and p-ERK1/2 were significantly reduced by the co-transfection of si-FGF7. Furthermore, the application of LY3214996, the inhibitor of ERK also verified these outcomes. MiR-381-3p directly targeting FGF7 modulated the osteogenic differentiation via MEK/ERK signaling pathway in BMMSCs. Highlights: The effect of miR-381-3p on the osteogenic differentiation of MSCs in MBD was clarified in this article. The BM-MSCs from MBD or normal participants were induced to differentiation with dexamethasone. MiR-381-3p directly targeting FGF7 modulated the osteogenic differentiation via MEK/ERK signaling pathway in MBD-MSCs.